Siphorex carving workshop - Prajapati, Sandeep (New Panvel AIKTC, School of Architecture, 2018)
Learning eResources created by AIKTC faculty.
Keywords: ARCHITECTURE EDUCATION (AR-EDU); Electronic Resources